Study protocol: the effectiveness and cost effectiveness of a brief behavioural intervention to promote regular self-weighing to prevent weight regain after weight loss: randomised controlled trial (The LIMIT Study) - Madigan, Claire D (BMC Public Health, 2015)
BACKGROUND: Although obesity causes many adverse health consequences, modest weight loss reduces the incidence. There are effective interventions that help people to lose weight but weight regain is common and long term maintenance remains a critical challenge. As a high proportion of the population of most high and middle income countries are overweight, there are many people who would benefit from weight loss and its maintenance. Therefore, we need to find effective low cost scalable interventions to help people achieve this. One such intervention that has shown promise is regular self-weighing, to check progress against a target, however there is no trial that has tested this using a randomised controlled design (RCT). The aim of this RCT is to evaluate the effectiveness and cost effectiveness of a brief behavioural intervention delivered by non-specialist staff to promote regular self-weighing to prevent weight regain after intentional weight loss. METHODS: A randomised trial of 560 adults who have lost ≥5 % of their initial body weight through a 12 week weight loss programme. The comparator group receive a weight maintenance leaflet, a diagram representing healthy diet composition, and a list of websites for weight control. The intervention group receive the same plus minimally trained telephonists will ask participants to set a weight target and encourage them to weigh themselves daily, and provide support materials such as a weight record card. The primary outcome is the difference between groups in weight change from baseline to 12 months. DISCUSSION: If effective, this study will provide public health agencies with a simple, low cost maintenance intervention that could be implemented immediately. TRIAL REGISTRATION: ISRCTN52341938 Date Registered: 31/03/2014